Long-range states in excited ultracold 3He*–4He* dimers. (28th April 2015) - Cocks, D G; Peach, G; Whittingham, I B
Abstract: Long-range bound states of the excited heteronuclear – He* system that dissociate to either (1s2s S1 ) + (1s2p P j ) or (1s2p P j ) + (1s2s S1 ), where, are investigated using both single-channel and multichannel calculations in order to analyse the effects of Coriolis and non-adiabatic couplings. The multichannel calculations predict two groups of resonances above the lowest asymptotic energy. One of these groups dissociates to an atomic pair with the 2p excitation on the fermionic atom and the other dissociates to two asymptotes which correspond to the 2p excitation on either atom. Many of these resonances could be identified with levels in the single-channel calculation although the differences in energies were large. The total parity was found to have a significant influence on the ability to make these identifications. No purely bound states were found, although several resonances with line widths smaller than 1 MHz were obtained.